FULFILLMENT OF PRISONERS SEXUAL RIGHTS AND NEEDS: AN INTEGRATIVE ANALYSIS FROM A HUMAN RIGHTS AND ISLAMIC LAW PERSPECTIVE - Yusran; Abdul Wahid; Sitti Fatimah Maddusila; Kartini Malarangan (Referensi Islamika: Jurnal Studi Islam, 2026)
This study examines the fulfillment of the sexual needs of married prisoners through an integrative framework combining Human Rights principles and maqāṣid al-syarī‘ah. Using Class IIA Palu Penitentiary as a case study, it analyzes the legal, institutional, and socio-cultural factors contributing to the absence of policies regulating the maintenance of lawful marital relationships within the Indonesian correctional system. This research employed a qualitative socio-legal approach. Empirical data were collected through in-depth interviews with married prisoners and correctional officers, field observations, and analysis of relevant legal documents and correctional regulations. The empirical findings were integrated with normative legal analysis based on Human Rights principles and the maqāṣid al-syarī‘ah framework. The study reveals that neither Indonesian correctional regulations nor Class IIA Palu Penitentiary provides explicit legal or institutional mechanisms for fulfilling the sexual needs of married prisoners. This regulatory gap is shaped by the absence of specific legal provisions, institutional constraints, security considerations, and prevailing socio-cultural perspectives. The findings further demonstrate that maintaining lawful marital relationships contributes to protecting human dignity, preserving family integrity, and supporting prisoners' psychological well-being, provided that any future policy is implemented proportionately and remains consistent with correctional objectives, institutional security, and applicable legal principles. This study is limited to a single correctional institution; therefore, its findings cannot be generalized to all Indonesian prisons. Nevertheless, it provides a conceptual foundation for developing correctional policies that accommodate family relationship maintenance while balancing prisoners' fundamental rights, rehabilitation, institutional security, and public interests. This study contributes to the literature by integrating Human Rights principles and maqāṣid al-syarī‘ah within a socio-legal framework to examine the fulfillment of married prisoners' sexual needs in Indonesia. It proposes an Integrated Family Relationship Maintenance Framework to strengthen family preservation, human dignity, and rehabilitation within the Indonesian correctional system.